Socialization of Research Plan Arrangement of Curriculum 2013 Based on Technical Guide Preparation of Research Plan in Basic School - Siti Halidjah; Syamsiati Syamsiati (Universitas Tanjungpura, 2018)
The purpose of the implementation of community service is to provide an understanding of the preparation of the implementation plan of curriculum lesson 2013 based on the technical guidelines for the preparation of the implementation plan of learning in elementary school. The teachers involved amounted to 30 people and were representatives of several schools. Methods of activities carried out in the form of socialization by displaying resource persons who have competence in the field of preparation of curriculum learning implementation plan 2013. From the results of community service activities with the focus of the preparation of the implementation plan of learning Curriculum 2013, knowledge and understanding of teachers about the implementation plan of learning Curriculum 2013 better.